NEW DATA ON THE OSTEOLOGY AND DEVELOPMENT OF AVITABATRACHUS ULIANA (ANURA, XENOANURA), A PIPIMORPH FROM THE CANDELEROS FORMATION, CRETACEOUS OF NORTHWESTERN PATAGONIA, ARGENTINA (Ameghiniana, 2024)
Re-examination of the type skeleton of the pipimorph frog Avitabatrachus uliana Báez, Trueb, & Calvo, 2000 from the CandelerosFormation of northwestern Patagonia and consideration of recent evidence on the development of the sacro-urostylic complex in living anurans leads to a reinterpretation of the pattern of contact of sacrum and urostyle in young post metamorphs of this Cenomanian taxon and re-consideration of its diagnostic features. This re-examination of the slab on which the type specimen is preserved also enabled us to identify remains that represent a metamorphosing individual of the same species and provide evidence for the plesiomorphic configuration of the parasphenoid and the separate first two presacral vertebrae preceding fusion to one another, as in some other Cretaceous pipimorphs.